Engaging Social Leadership Character on Cadets Training during Onboard Based on Mobile Application Monitoring: A Preliminary Study: Pembentukan Karakter Kepemimpinan Sosial pada Pelatihan Kadet selama Onboard Berbasis Monitoring Aplikasi Mobile: Studi Pendahuluan - Sabaruddin; Jamil, T. M.; Nurmala, Eka; Baihaqi; Siregar, Muhammad Sapril (PT. Alpha Trianguli Australis, 2024)
This preliminary study delves into the effectiveness of mobile application monitoring in enhancing social leadership character among cadets during onboard training. The research focuses on the social dimension of character development, which encompasses the ability to act with proper decorum in all professional, social, and online environments. The study explores how mobile technology can facilitate experiential learning, teamwork, and leadership skills, improving cadets' social interactions and leadership abilities. The mixed-methods approach employed in this study combines quantitative data from mobile application usage with qualitative insights from cadet feedback and mentorship programs. This comprehensive methodology allows for a deeper understanding of the impact of mobile applications on cadets' social leadership development. The findings indicate that mobile applications can significantly enhance cadets' engagement in social leadership activities, improve their teamwork and problem-solving skills, and provide real-time feedback for character development. Moreover, the study highlights the potential of mobile technology to support comprehensive character development in cadet training programs. By leveraging mobile applications, training programs can create a more immersive and interactive learning environment that fosters the development of essential social leadership skills. The results of this study have significant implications for educational institutions and military academies seeking to enhance their cadet training programs and prepare future leaders with robust social leadership capabilities. Overall, this preliminary study underscores the importance of integrating mobile technology into cadet training to promote social leadership character development, thereby equipping future leaders with the skills to navigate complex social environments effectively.